2013
DOI: 10.1186/1746-6148-9-63
|View full text |Cite
|
Sign up to set email alerts
|

Effect of L-arginine on HSP70 expression in liver in weanling piglets

Abstract: BackgroundThis study was conducted to evaluate the effects of L-arginine (Arg) on photomicrographs and HSP70 expression in the liver of weanling piglets. Twelve healthy Landrace × Yorkshire piglets that had been weaned at 21 d (average body weight 5.56 ± 0.51 kg) were randomly divided into a control group and an Arg group (6 g/kg feed). At age 28 d, all of the piglets were slaughtered to obtain liver samples to determine HSP70 expression by real-time PCR, western blot and immunohistochemistry.ResultsThe result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…This result may indicate the cytoprotective beneficial impact of these agents against hypoxia induced renal tissue injury. There is an evidence that carnosine and arginine can regulate intracellular HSP-70 expression which is essential for preventing organ dysfunction (Chatterjee et al 2005;Mikami et al 2006;Wu et al 2013) . The current result also revealed that a marked elevation in the serum HIF-1α of hypoxic rats compared with normal animals.…”
Section: Discussionmentioning
confidence: 99%
“…This result may indicate the cytoprotective beneficial impact of these agents against hypoxia induced renal tissue injury. There is an evidence that carnosine and arginine can regulate intracellular HSP-70 expression which is essential for preventing organ dysfunction (Chatterjee et al 2005;Mikami et al 2006;Wu et al 2013) . The current result also revealed that a marked elevation in the serum HIF-1α of hypoxic rats compared with normal animals.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, treatment of pigs with mold-contaminated feed has adverse effects on growth performance, structure of the intestine (histology, morphology and barrier function), and serum amino acid profile. Glutamate likes other functional amino acids can improve animal health [60] [77] . Dietary supplementation with glutamate partially counteracts the impairments induced by mycotoxins.…”
Section: Discussionmentioning
confidence: 99%
“…Western blotting were performed as described previously [17]. The membranes were incubated with primary antibodies, including total mTOR (#2972; Cell Signaling Technology), p-mTOR (#5536; Cell Signaling Technology), p-4EBP1 (#9451; Cell Signaling Technology), p-p70S6K (ab126818; Abcam) and β-actin (sc-47778; Santa Cruz) antibodys at 1:1000 dilution.…”
Section: Methodsmentioning
confidence: 99%